Study of PI3K/AKT/mTOR pathway in breast cancer progression - Novaro, Virginia (2018)
Deregulation in the PI3K/AKT/mTOR pathway is associated with breast cancer development. Using experimental models of breast carcinogenesis induced in mice, xenografts of tumor cell lines, and tumors from patients we found a differential role of AKT1 and AKT2 isoforms in breast cancer progression. That is, AKT1 regulates nuclear proteins related to cell proliferation, such as cyclin D1 and pS6, whereas AKT2 regulates proteins related to cell migration and invasion such as vimentin, integrin b1, F-actin and FAK. Furthermore, activation of AKT1 promoted the hormone-independent and endocrine resistant phenotype, whereas activation of AKT2 lead to a more aggressive phenotype and lung metastasis. We analyzed 98 luminal breast carcinomas and found that nuclear AKT1 associates with low grade tumors, while cytosolic AKT2 associates with high grade tumors. Furthermore, presence of cytosolic AKT2 was positively correlated with a shorter time to progression of the disease (earlier relapse). In addition, based on our results and data analysis from public databases of The Cancer Genome Atlas, we postulate that throughout the progression of the disease there would be a switch between AKT1 and AKT2 isoforms, which maintains AKT2 inhibited while AKT1 prevails in the early stages. In the more advanced stages, this inhibition is lost and AKT2 prevails. Specific miRNAs are good candidates involved in this regulation and are now been tested in our lab in different experimental and clinical conditions. We propose the use of AKT1 and AKT2 isoforms determined by immunohistochemistry as prognostic markers that could help to better stratify breast tumors and direct more specific therapies.